Population genetics of the endemic and endangered Vriesea minarum (Bromeliaceae) in the Iron Quadrangle, Espinhaço Range, Brazil - Lavor, Pâmela; van den Berg, Cássio; Jacobi, Claudia M; Carmo, Flávio F; Versieux, Leonardo M (American journal of botany, 2014)
• Premise of the study: Knowledge about genetic variability in plant populations is one of the main branches of conservation genetics, linking genetic data to conservation strategies. Vriesea minarum is a bromeliad endemic to the Iron Quadrangle region (southeastern Brazil), occurring on mountaintop rock outcrops. It is listed as endangered due to habitat loss, particularly from iron ore mining. Thus, determining the structure and genetic diversity of V. minarum populations could help develop strategies to conserve the species.• Methods: We studied the genetic structure of 12 populations of V. minarum using 10 microsatellite loci transferred from other species of Bromeliaceae. Statistical analyses to compare and describe the genetic diversity of each population were performed, and genetic structure within and among populations, isolation by distance, and Bayesian structure were also analyzed.• Key results: Our results show high inbreeding (GIS = 0.376) and low population structure (FST = 0.088), possibly related to high gene flow due to great pollinator efficiency and/or efficient seed dispersal, thus leading to high connectivity among populations of these fragmented rock outcrops. Two clusters were observed, corresponding to the basins of rivers São Francisco and Doce.• Conclusions: Gene flow among populations is high but, given the rate of habitat loss to mining, most populations are vulnerable and will become increasingly isolated if no action is taken to preserve them. Thus, conservation of this species depends on in situ and ex situ actions, such as controlling overexploitation and creating a germoplasm bank.